Evaluation of lodging resistance in rice based on an optimized parameter from lodging index. Issue 3 (20th March 2022) - Luo, Xiaoyun; Wu, Zefang; Fu, Lu; Dan, Zhiwu; Yuan, Zhengqing; Liang, Ting; Zhu, Renshan; Hu, Zhongli; Wu, Xianting
Abstract: Lodging is being increasingly recognized as a critical concern among crop breeders worldwide as it causes a significant reduction in the grain yield and quality of multiple cereal crops. The lodging index is frequently used for evaluating the lodging resistance of rice ( Oryza sativa L.) crops. However, the application of lodging index for comparing lodging susceptibility between different rice cultivars is inadequate under certain special conditions. This study was aimed to identify optimized parameters that would evaluate the lodging susceptibility and could then be used along with the lodging index for further assessing the lodging resistance. A total of 32 representative rice accessions from different countries were grown at two different locations on three different sowing dates over a period of 3 yr. The analysis of the lodging index of the different rice cultivars revealed the lodging index value of 200 as the critical threshold value of the evaluated rice accessions. Subsequently, an optimized parameter from the lodging index was proposed. This parameter could be interpreted as the magnitude of the external force that the basal second internode could withstand. A comparison of the optimized parameter values of different rice accessions revealed a previously unknown lodging‐resistant variety R379. The application of the optimized parameter would enable an accurate determination and comparison of the lodging resistance among different rice cultivars, thereby contributing to the effective selection of lodging‐resistant cultivars in rice breeding programs. Core Ideas: Lodging index is unsuitable for evaluating lodging resistance under certain special conditions. The lodging index value 200 was observed to be the threshold for lodging in the field trials. We identified a previously unknown lodging‐resistant variety R379 by the optimized parameter. Improving the breaking resistance of the basal internodes is the basis for lodging resistance.